Factors affecting consumption patterns of neglected and underutilized species in Atacora, Northern Benin - Bankole, Bissola Malikath; Bodjrenou, Sam; Bodecker, Julia; Termote, Celine; Chadare, Flora Josiane; Amoussa Hounkpatin, Waliou (2023)
Presented at the 5th Conference of the Federation of African Nutrition Societies, November 2023, Dakar, Senegal. To solve food security issues, many efforts have been made in recent years to improve the use of neglected and underutilized species (NUS) in people's diets, given their significant contribution to nutrient intake. On the other hand, their consumption by the population could be influenced by many factors. With this in mind, this study aims to understand the factors associated with the consumption patterns of Adansonia digitata, Ocimum gratissimum, Vigna radiata and Moringa oleifera by households in Atacora, northern Benin.